A helyi pénz gazdaságtörténeti vonatkozásai - Szávai, Ferenc (Acta Scientiarum Socialium, 2013)
On the role of local currencies numerous controversial articles have been published by now, many of which question its justification. This paper endeavours to grasp its significance and to place it in economic history. Following Gessell the significance of local currencies becomes clearer: besides the European cooperative idea the bank of the poor and the Islamic bank show similar characteristics. Great crises always point to simple solutions. Such solutions are tracked until 2025 by the paper. The hypothesis is that this „old brand new” concept in economic historyâ€”local currencyâ€”has an important role to play in the present day crisis management.
Keywords: local currency; Great Crisis; cooperation; Raiffeisen; monetary banking system; economic history; gentle money; Silvio Gesell